Virtuous Activity Is Sufficient for Happiness and Some Minimally Favorable Circumstances Are Necessary for Virtuous Activity - Hole, Benjamin Visscher (My University, 2016)
I argue for a nontraditional sufficiency thesis: virtuous activity is sufficient for happiness and some minimally favorable circumstances are necessary for virtuous activity. This view satisfies two intuitions from the ancient dispute that might at first seem in tension. Happiness depends on favorable external circumstances, and virtuous activity guarantees happiness.
Thesis (Ph.D.)--University of Washington, 2016-08
Keywords: circumstances; embodiment; happiness; virtue ethics; Philosophy; philosophy